Dietary intake of soccer players: Effects of competition level and playing position - Souglis, G. A.; Maridaki, M.; Chryssanthropoulos, C.; Tsalouhidou, S.; Sotiropoulos, A.; Mougios, V. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The present study examined the effect of competition level and position of play on dietary intake of male soccer players (SP). Methods A total of 136 SP weighed and recorded their diet for 3 days: the day before a formal match, on match day, and the day after the match. After exclusion of 13 SP as underreporters the diets of 123 SP were considered. Results & Discussion When data were analyzed for competition level SP in the Super League Division (SL, n=33) reported higher daily energy [195 + 6 kJ/kg BM (Body Mass); p< 0.01], carbohydrate (6.0 + 0.2 g/kg BM; p< 0.01), and protein ( 2.2 + 0.1 g/kg BM; p< 0.05) intakes compared to SP in the 2nd (n=30) (energy: 159 + 6 kJ/kg BM; carbohydrate: 4.6 + 0.2 g/kg BM; protein: 1.9 + 0.1 g/kg BM), 3rd (n=30) (energy: 153 + 6 kJ/kg BM; carbohydrate: 4.5 + 0.2 g/kg BM; protein: 1.7 + 0.1 g/kg BM), and 4th (n=30) (energy: 152 + 7 kJ/kg BM; carbohydrate: 4.2 + 0.2 g/kg BM; protein: 1.7 + 0.1 g/kg BM) national category (NC)(mean + SE). Furthermore, the energy derived from carbohydrates was higher (p< 0.01) in the SL players (51 + 1 %) compared to the 4th NC players (46 + 1 %), whereas the energy derived from fat was lower (29 + 1 %) (p< 0.01) in the SL compared to the 4th NC players (34 + 1 %). When data were analyzed for playing position, after excluding the 5 goalkeepers, energy and carbohydrate intakes were higher (p< 0.01) for the wide midfielders (n=24) (energy: 183 + 7 kJ/kg BM; carbohydrate: 5.4 g/kg BM) compared to the central defenders (n=23) (energy: 147 + 8 kJ/kg BM; carbohydrate: 4.1 + 0.2 g/kg BM), whereas no differences were found among the other three positions (full backs/n=24, central midfielders/n=24, and attackers/n=23) for the other macronutrients. With the exception of SL players, the SP in the other professional (2nd and 3rd NC) and semi-professional (4th NC) levels did not meet the carbohydrate intake guidelines1. Conclusion The dietary intake of SP may differ according to playing position and competition level possibly due to different physiological demands.